THE EFFECT OF SERVANT LEADERSHIP AND COMPENSATION ON EMPLOYEE PERFORMANCE THROUGH ORGANIZATIONAL COMMITMENT (Study at PT Cometic Perkasa Abadi Semarang) - Careza Rizky Ayuningtyas; Frans Sudirjo; Nurchayati Nurchayati (Proceeding of The International Conference on Business and Economics, 2023)
This study aims to analyze the influence of servant leadership and compensation on employee performance either directly or through organizational commitment. The population in this study is 122 people. The size of the sample is 93 respondents. The data source used is primary data with questionnaire data collection method which gather using the simple random sampling techniques. The analysis technique used is path analysis. The results of the research showed that servant leadership and compensation has a positive and significant effect on organizational commitment. Servant leadership and compensation has a positive and significant effect on employee performance. The Sobel test results indicated that the variable of organizational commitment can mediate the influence of servant leadership and compensation on employee performance.